Preparation of Alumina Nanoparticles and Coating with Polyvinylpyrrolidone to Treat Cadmium Contamination of Water - Shaymaa Mohammed Fayyadh; Foud Nihad Abed; Emaad Muhamme Awsaj; Samar S. Mohammed; Abdulsattar Abdullah Hamad Mohamad; M. Mahdi Abdulridha; Sameer Alshehri; Gashaw Tadele; Wegayehu Enbeyle (Adsorption Science & Technology)
Alumina nanoparticles were prepared by sol-gel method, where the obtained nanosize was 35 nm, and the nanomaterial was coated with PVP polymer, where the nanomaterial was dispersed by ultrasonic waves for half an hour, and then, the polymer was added, and under high magnetic stirring for 24 hours, it was dried at a temperature of 60°C for 24 hours. Cadmium salt solutions were prepared with different concentrations of 10, 30, and 60 ppm, and the nanomaterial was immersed in the prepared solutions at different times of 10, 30, and 60 minutes, and the measurement was done by an atomic absorption device. By means of the electronic scanner, a difference appeared in the nanosize, and this indicates that the packaging has completely occurred.